Anti-inflammatory Effect of Obestatin and Ghrelin in Dextran Sulfate Sodium-Induced Colitis in Rats - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2013)
Background and Objectives:Obestatin and ghrelin are hormones derived from the same gene but have opposing effects. Ghrelin has anti-inflammatory activities; however, the role of obestatin in the inflammatory processes has not been clearly demonstrated yet. The aim of the study was to analyse and compare the anti-inflammatory effect of exogenous ghrelin and obestatin in a rat model of colitis.Methods:Acute and chronic colitis was induced in 96 rats by adding 3% dextran sulfate sodium to the drinking water for 5 and 10 days, respectively. Intraperitoneal pretreatment with ghrelin or obestatin was started before the induction of colitis, and continued for 5 and 10 days. Clinical signs of the disease and histopathological changes were evaluated. By-products of neutrophil activation, lipid peroxidation, and inflammatory and anti-inflammatory cytokines were measured in colonic tissues.Results:Obestatin and ghrelin significantly ameliorated clinical and histopathological severity of chronic colitis, whereas they were less effective in the acute form. Therapeutic effect of ghrelin and obestatin in acute colitis was associated with reduced lipid peroxidation and T(h)1-induced inflammatory response, whereas obestatin in chronic colitis was protective via the suppression of polymorphonuclear leukocyte infiltration and enhancement of glutathione synthesis. Moreover, therapeutic effects of ghrelin and obestatin in chronic colitis appear to be associated with inhibition of inflammatory and activation of anti-inflammatory cytokines.Conclusions:This study demonstrated the novel anti-inflammatory effect of obestatin and ghrelin in an experimental model of colitis. Although both obestatin and ghrelin exerted anti-inflammatory effects in chronic colitis, they were less effective in acute colitis.
Keywords: colitis; dextran sulfate sodium; ghrelin; obestatin; rats; INFLAMMATORY-BOWEL-DISEASE; ULCERATIVE-COLITIS; ORGAN INJURY; INDUCED GASTROPROTECTION; ISCHEMIA-REPERFUSION; T-CELLS; EXPRESSION; MODEL; INTERLEUKIN-10; ACTIVATION